2011
DOI: 10.1161/atvbaha.111.232835
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Smooth Muscle Cell Migration During Arteriogenesis Is Mediated by Rap2

Abstract: Objective-Collateral artery growth or arteriogenesis is the primary means of the circulatory system to maintain blood flow in the face of major arterial occlusions. Arteriogenesis depends on activation of fibroblast growth factor (FGF) receptors, but relatively little is known about downstream mediators of FGF signaling. Methods and Results-We screened for signaling components that are activated in response to administration of FGF-2 to cultured vascular smooth muscle cells (VSMCs) and detected a significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…3E). In line with these findings, differential responses of smooth muscle cells with respect to proliferation and migration in vitro have been observed previously [32][34]. In addition, permanent adaptive molecular changes during development of mdx smooth muscle to compensate for the lack of dystrophin may enable the cells to migrate, but not proliferate more efficiently in vitro .…”
Section: Resultssupporting
confidence: 78%
“…3E). In line with these findings, differential responses of smooth muscle cells with respect to proliferation and migration in vitro have been observed previously [32][34]. In addition, permanent adaptive molecular changes during development of mdx smooth muscle to compensate for the lack of dystrophin may enable the cells to migrate, but not proliferate more efficiently in vitro .…”
Section: Resultssupporting
confidence: 78%
“…Rap1a and Rap1b proteins have been shown to be upregulated by PDGF in vascular smooth muscle cells, and this upregulation during the smooth muscle cell cycle is directly linked to cell proliferation (378). PDGF and FGF-2 also induce an increase in Rap2 during late S phase and G 2 /M phase of the smooth muscle cell cycle (368). Silencing of Rap2 indicated that Rap2 is required for migration but not for vascular smooth muscle cell proliferation.…”
Section: Ras Proteinsmentioning
confidence: 98%
“…Firstly, we found that VNS-induced VEGF-A/B expression cooperatively regulated angiogenesis and arteriogenesis in infarcted heart. Secondly, VNS-triggered angiogenesis and arteriogenesis improved the coronary function Collateral artery growth or arteriogenesis is the primary approach for coronary arteries to maintain blood flow in the event of coronary arterial occlusions, being responsible for myocardium infarction [34]. An occluded artery is not normally replaced by one single large collateral vessel but rather by several smaller ones [30].…”
Section: Discussionmentioning
confidence: 99%